The Arabic Version of the Nicomachean Ethics - Akasoy; Fidora, Alexander (Aristoteles Semitico-Latinus, 2005)
This volume offers a critical edition of the only extant Arabic manuscript of the Nicomachean Ethics. A comprehensive introduction by the late Douglas M. Dunlop describes the influence this major Aristotelian work had on Arabic literature. Dunlop's annotated English translation includes important references to the Greek text of the Ethics. The appendix includes a select Greek-Arabic glossary.